Prevalence and socio-economic factors associated with Gender-based Violence against irregular Venezuelan migrant pregnant women in the Colombian Caribbean (2020)
Introduction: Human migration, especially when forced and irregular, can increase violence perpetrated against women. The current migration phenomenon between Colombia and Venezuela is a massive migration, with a high participation of women, a large part of them in irregular condition and socioeconomic vulnerability to Gender-Based Violence (GBV). This study describes the characteristics of Venezuelan migrant pregnant women in the two main receiving cities of the Colombian Caribbean (Barranquilla and Riohacha), as well as estimates the prevalence of GBV. Finally, the main associated socioeconomic factors are identified. Methodology: cross-sectional study with application of a structured closed questionnaire to 836 irregular migrant pregnant women that included questions about violence, as well as its socio-economic determinants. Logistic regression models were adjusted for the presence of each form of violence. Results: Psychological violence (81.4%) followed by economic violence (35.3%) were the most prevalent. On the other hand, physical violence had a prevalence of 14.5% and sexual violence of 2.2%. In the logistic regression models, a statistically significant association of low educational level with the occurrence of physical violence was found, the strength of association being greater with those with an elementary educational level (OR: 5.51; 95% CI: 2.10-14.49) , followed by secondary or technical (OR: 3.18; 95% CI: 1.24-8.17). Conclusions: These results reveal the need to incorporate a gender perspective into the analysis of migrations and interventions in Public Health, which considers the greatest vulnerability of women with low educational level.